Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have this inequality that i don't know how to prove. Possibly the inequality between means might be useful. For $n \in \mathbb{N}$:

$$\frac{1}{n+1}+\frac{1}{n+2}+...+\frac{1}{3n+1} \ge 1$$

share|improve this question
    
if you want to use inequalities between means: use the inequality between arithmetic and harmonic mean and compute/estimate the harmonic mean of $1/(n+1),\dots,1/(3n+1)$ –  user8268 Oct 28 '12 at 19:25
    
Try using mathematical induction. –  Jonah Sinick Oct 28 '12 at 20:10

4 Answers 4

up vote 1 down vote accepted

It follows immediately from arithmetic mean harmonic mean inequality. Recall that given a set of positive numbers, $\{a_k\}_{k=1}^{k=m}$, we have that $$\dfrac{\displaystyle\sum_{k=1}^{m} a_k}m \geq \dfrac{m}{\displaystyle \sum_{k=1}^m \dfrac1{a_k}}$$ $$\dfrac{\displaystyle \sum_{k=1}^{2n+1} \dfrac1{n+k}}{2n+1} \geq \dfrac{2n+1}{\displaystyle \sum_{k=1}^{2n+1} (n+k)}$$ $$\displaystyle \sum_{k=1}^{2n+1} (n+k) = n(2n+1) + \dfrac{(2n+1)(2n+2)}2 = (2n+1)^2$$ Hence, $$\dfrac{\displaystyle \sum_{k=1}^{2n+1} \dfrac1{n+k}}{2n+1} \geq \dfrac{2n+1}{(2n+1)^2}$$ Hence, $$\displaystyle \sum_{k=1}^{2n+1} \dfrac1{n+k} \geq 1$$

share|improve this answer

Write this as $$ \sum_{j=1}^{2n+1} \dfrac{1}{n+j} \ge \int_1^{2n+2} \dfrac{dx}{n+x} = \ln \left(\frac{3n+2}{n+1}\right)$$

Now $\dfrac{3n+2}{n+1} \ge e$ for $n > \dfrac{e-2}{3-e} \approx 2.549$. Do the cases $n=1$ and $2$ separately.

share|improve this answer

We induct on $n$. For $n=1$, it's trivial. Now assume it holds for $n=k$, then $$ \frac{1}{(k+1)+1}+\cdots+\frac{1}{3(k+1)}+\frac{1}{3(k+1)+1}=\frac{1}{k+2}+\cdots+\frac{1}{3k+4} $$ $$ =(\frac{1}{k+1}+\cdots+\frac{1}{3k+1})-\frac{1}{k+1}+\frac{1}{3k+2}+\frac{1}{3k+3}+\frac{1}{3k+4} $$ Since the first expression is at least $1$ by the inductive hypothesis, it suffices to show $$ \frac{1}{3k+2}+\frac{1}{3k+3}+\frac{1}{3k+4}\ge \frac{1}{k+1} $$ But by Cauchy-Schwarz we obtain $$ (3k+2+3k+3+3k+4)(\frac{1}{3k+2}+\frac{1}{3k+3}+\frac{1}{3k+4})\ge9 $$ Which is equivalent to what we want after dividing by $9(k+1)$. So the inductive hypothesis always holds.

We can also use user8268's hint and apply Cauchy or AM-HM directly: $$ (k+1+\cdots+3k+1)(\frac{1}{k+1}+\cdots+\frac{1}{3k+1})\ge (2k+1)^2 $$ So it suffices to show $$ (2k+1)^2\ge (k+1+\cdots+3k+1)=(1+\cdots+3k+1)-(1+\cdots+k) $$ or $$ 4k^2+4k+1\ge \frac{(3k+1)(3k+2)}{2}-\frac{k(k+1)}{2}=\frac{8k^2+8k+2}{2}=4k^2+4k+1 $$ but this is clearly true.

share|improve this answer
    
I tried this method as well but the second inequality is not true. Let's put k=6, then we get: $$L=\frac{1}{20}+\frac{1}{21}+\frac{1}{22} \approx 0.14$$ while the right side is $$ R=\frac{1}{7} \approx 0.16$$ –  Max Oct 28 '12 at 19:43
    
Actually, $L=\frac{1}{20}+\frac{1}{21}+\frac{1}{22}\approx 0.1431$, while $R=\frac{1}{7}\approx 0.1429$, so I believe the inequality is true. –  pi37 Oct 28 '12 at 19:54
    
Yes indeed, you are right. Actually i did this exercise the same way you have, but instead of $\frac{1}{k+1}$ I, somehow, got $\frac{1}{k}$ for which this inequality is not true. Thanks! –  Max Oct 28 '12 at 20:08

In general, if $f$ is a convex function and $p_j$ are non-negative coefficients such that $\sum p_j = 1$ then

$$ \sum_j p_j \, f(x_j) \geq f(\sum_j p_j \, x_j). $$

(This is Jensen's inequality.) Take $f(x) = 1/x$, $p_j = 1/(2n + 1)$ and $x_j = n + j$ for $j \in \{1, \dotsc, 2n+1 \}$ and your inequality follows.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.